Axon Guidance and Collective Cell Migration by Substrate-Derived Attractants - Aberle, Hermann (Frontiers in Molecular Neuroscience, 2019)
Neurons have evolved specialized growth structures to reach and innervate their target cells. These growth cones express specific receptor molecules that sense environmental cues and transform them into steering decisions. Historically, various concepts of axon guidance have been developed to better understand how axons reach and identify their targets. The essence of these efforts seems to be that growth cones require solid substrates, and that major guidance decisions are initiated by extracellular cues. These sometimes highly conserved ligands and receptors have been extensively characterized and mediate four major guidance forces: chemoattraction, chemorepulsion, contact attraction and contact repulsion. However, during development, cells, too, do migrate in order to reach molecularly-defined niches at target locations. In fact, axonal growth could be regarded as a special case of cellular migration, where only a highly polarized portion of the cell is elongating. Here, I combine several examples from genetically tractable model organisms, such as Drosophila or zebrafish, in which cells and axons are guided by attractive cues. Regardless, if these cues are secreted into the extracellular space or exposed on cellular surfaces, migrating cells and axons seem to keep close contact to these attractants and seem to detect them right at their source. Migration towards and along such substrate-derived attractants seem to be particularly robust, as genetic deletion induces obvious searching behaviors and permanent guidance errors. In addition, forced expression of these factors in ectopic tissues is highly distractive too, regardless of the pattern of other endogenous cues. Thus, guidance and migration towards and along attractive tissues is a powerful steering mechanism that exploits affinity differences to the surroundings and, in some instances, determines growth trajectories from source to target region.